Optimization of Mechanical Properties of Aluminium Hybrid Metal Matrix Composite and Its Major Applications - Anil Singh; Dr. Rupinder Singh Johal; Sulekha (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This article describes how to optimize the mechanical properties of aluminium hybrid metal matrix composite (Al-HMMC) in order to reduce weight and cost while increasing the material’s strength, stiffness, toughness, and durability. “Some optimization techniques and applications are presented in this article; Matrix alloy optimization, processing parameter optimization, and surface treatment optimization are examples of hybrid reinforcement optimization that display different elements that influence the optimizations and their methods. The influence of different factors and the need for large experimental data sets are also covered in this article, with reference to earlier research. The major applications of Al-HMMC, including the automotive, sports, marine, and aerospace industries, as well as industrial automation for components and its future directions, are also covered in this article. This essay came to the conclusion that the most crucial aspect of engineering for resolving complicated problems is feature modeling, estimate, and optimization. When designing and optimizing the process variables to be employed throughout the manufacturing phase, significant benefits of the calculating methodologies are identified. Optimal parameter selection, system placement, result analysis, production digitization, power consumption reduction, and real-world issue resolution are all made possible by these techniques.” Therefore, additional study is required in the future to optimize the structure and composition of hybrid reinforcement in order to attain better mechanical characteristics.